Partying, Cruising, and Hanging in the Streets: Gangs, Routine Activities, and Delinquency and Violence in Chicago, 1959–1962 - Hughes, Lorine A. (Journal of quantitative criminology, 2014)
Objectives Examine relationships between routine activities, character contests in the form of “signifying,” and general delinquency and fighting in a street gang context. Methods Samejima’s (Estimation of latent ability using a response pattern of graded scores. Psychometrika monograph supplement 17. Psychometric Society, Richmond, VA, Retrieved 10 Aug 2011, from http://www.psychometrika.org/journal/online/MN17.pdf , 1969 ) graded response models and multilevel ordinal logistic regression models are estimated using data from Short and Strodtbeck (Group process and gang delinquency. University of Chicago Press, Chicago, 1965 ) study of street gangs in Chicago, 1959–1962. The primary sample consists of 490 boys representing 10 black gangs, 4 white gangs, 9 black lower-class groups, 4 white lower-class groups, 2 black middle-class groups, and 2 white middle-class groups. Results Unstructured and unsupervised socializing with peers significantly increased the likelihood of delinquency among the boys and explained a significant portion of the group-level gang effect. In addition, the more time the boys spent hanging in the streets and attending parties, the more likely they were to participate in signifying, which, in turn, increased their risk of fighting. Conclusions Findings provide evidence that gangs contribute to delinquency partly through their effect on the routine activities of members. Findings also suggest that signifying is an important mechanism by which unstructured and unsupervised socializing with peers leads to violence.